Identifikasi Keanekaragaman Tumbuhan Talas (Colocasia Esculenta L) di Wilayah Kampung Sayal Distrik Saifi Kabupaten Sorong Selatan - Saflesa, Pascalina; Ulfa, Nurul Alia; Sutardi, Sutardi (STKIP HARAPAN BIMA, 2025)
The purpose of this study is to determine the diversity of taro plants in the Sayal village area of the Saifi district in Sorong regency. The type and design of this study is descriptive exploratory, which aims to describe the diversity of taro plants. It was conducted in May 2022, in the Sayal village area of the Saifi district, South Sorong regency. The sample for this study was all taro plant varieties classified under theColocasia genus. Data collection was carried out through the selection of study objects (STO) and the observation and scoring of taro morphological characters. Data were analyzed quantitatively using descriptive methods by calculating the similarity index to determine the level of similarity and varietal diversity. The results of this study can be summarized as follows: there are three types of taro plants in the Sayal village area of the Saifi district, Sorong Regency, from three villages, namely Komagaret village(Bogor taro), Baibet village (Belitung taro), and Sayal village(swamp taro).